Australian dams and reservoirs within a global setting. Issue 1 (2nd January 2020) - McMahon, T. A.; Petheram, C.
ABSTRACT: There has been a resurgence of interest in the construction of large dams worldwide. This study examined many dams from around the world (>10, 000) and compared them to a comprehensive dataset developed for Australia (224) to provide insights that might otherwise not be apparent from examining just one or several dams. The dam datasets (ICOLD and ANCOLD) largely confirm existing narratives on Australian dam construction. Compared to dams from Rest of the World (RoW), Australian dams were found to: have larger reservoir capacities and spillway capacities for a given catchment area; have higher dam walls for a given capacity; and result in higher degrees of river regulation. A range of general relationships among reservoir capacities, reservoir surface areas, and catchment areas are presented which can be used in reconnaissance or pre-feasibility studies and for global hydrologic modelling when dam and reservoir information are required as input.